Happiness is the way how to reframe your thinking and work with what you already have to live the life of your dreams - DYER, WAYNE W. (Hay House, 2019)
One of Dr. Wayne Dyer's favourite quotes was "When you change the way you look at things, the things you look at change." In this book, which collects some of Wayne's most classic teachings in paperback edition for the first time, you will find a novel solution for most any problem you may be encountering. Wayne covers many aspects of life, from how to respond with ability to finding the mission of your life and redefining success, he provides comfort, reassurance, and a fresh perspective on the pursuit of happiness. For, as Wayne was also fond of saying,"There is no way to happiness. Happiness is the way."